Description of the Implementation of Interpersonal Communication between Registration Officers and Elderly Patients at the Outpatient Registration Area of Hospital X - Desi Novitasari; Andi Suhenda; Gugun Priyadi; Ateng Mjutaqin (Poltekkes Kemenkes Tasikmalaya, 2025)
Background: A hospital is a healthcare facility that provides emergency, inpatient, and outpatient services. Before receiving outpatient services, patients must first register at the outpatient registration counter. Communication between the registration officer and the patient is crucial to understanding the patient's needs and complaints. Interpersonal communication is verbal and nonverbal communication that mutually influences the perception of the other person. The effectiveness of interpersonal communication is characterized by openness, support, a positive attitude, empathy, and equality. This is especially important for elderly patients who often experience physical and psychological decline. This study aims to describe the implementation of interpersonal communication between registration officers and elderly patients at the outpatient Registration Area of Hospital X. Methods: This research used a qualitative method with a case study design. Data collection was conducted through observation, interviews, and documentation, using a purposive sampling technique for informants. Results: The research results show that interpersonal communication between registration staff and elderly patients, in terms of positive attitudes, empathy, and equality, is already well-functioning. However, openness and support are still less effective, as registration services are conducted daily as a routine, leading staff to prioritize efficiency. Meanwhile, support remains spontaneous and has not yet become a habit. Conclusion: Interpersonal communication between registration staff and elderly patients is generally good, particularly in terms of positive attitudes, empathy, and equality. However, openness and support still need improvement